2007
DOI: 10.3892/or.17.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of Chk1, Chk2, Apaf1 and Rb1 in human malignant melanoma cell lines

Abstract: Abstract. Four tumour suppressor genes (Chk1, Chk2, Apaf1 and Rb1) in nine human malignant melanoma cell lines were screened for a loss of gene expression, point mutations and small deletions/insertions by cDNA-based DGGE/SCCP analysis. In two cell lines alterations of the investigated genes could be demonstrated. This result confirms our assumption of the participation of dysfunctional p53 inducer/effector genes in human melanoma aetiology. Furthermore, it points towards the probable principal role of diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…It was also shown that CHK1 and CHK2 expression was downregulated by promoter hypermethylation in glioma (51). Mutations in genes encoding both proteins were also found in metastasized melanoma cells (54).…”
Section: Discussionmentioning
confidence: 95%
“…It was also shown that CHK1 and CHK2 expression was downregulated by promoter hypermethylation in glioma (51). Mutations in genes encoding both proteins were also found in metastasized melanoma cells (54).…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand changes present only in invasive melanomas are probably responsible for tumor invasion and eventual metastasis. Presence of characteristic deletion of 13q that contains tumor suppressor gene Rb1 is interesting, as the Rb1 gene has been shown to be lost in some melanoma cell lines and is known contributing to dysfunctional p53 pathway 28 . Also, Rb1 was shown to be involved in melanocytic proliferation and pigmentation defect in vivo 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Presence of characteristic deletion of 13q that contains tumor suppressor gene Rb1 is interesting, as the Rb1 gene has been shown to be lost in some melanoma cell lines and is known contributing to dysfunctional p53 pathway. 28 Also, Rb1 was shown to be involved in melanocytic proliferation and pigmentation defect in vivo. 29 We propose that deletion or mutation of Rb1 might be one of the earliest events in the development of melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated that SNX-2112 mediates the degradation of Hsp90 client proteins and attenuates Akt/GSK3β, IKKα/NF-κB and MAPK signaling. Inhibition of these proteins is associated with reduced proliferation of melanoma cells (25)(26)(27)(28)(29). Both the Ras/Raf/MEK/Erk (MAPK) and the phosphatidylinositol 3-kinase (PI3K)/AKT signaling pathways are constitutively activated via multiple mechanisms in melanoma (30,31).…”
Section: Discussionmentioning
confidence: 99%